Strategi Implementasi Kebijakan Terhadap Tata Kelola Aset Syariah Tetap Pada Lembaga Badan Riset dan Inovasi Nasional (BRIN) di Jakarta - Gunawan, Ari; Andriyani, Andriyani (ITB AAS INDONESIA Surakarta, 2023)
This study aims to be mode orderly in administration, orderly in securing fixed assets, to get to the best opinion with no records of audit findings from external parties, namely the BPK. This research uses a qualitative method with a case study approach that occurred at ex-BPPT institutions in 2019 and 2020. This qualitative research methods uses primary data obtained from interviews, observation, documentation and secondary data obtained from documents. The results of the research are the findings from the BPK regarding the management of fixed assets in the ex-BPPT institutions had not been effective due to limited Human Resources in managing fixed assets or State Property. Implementation support with a commitment from the top leadership of the Head of BRIN as outlined in the form of policies and implementation guidelines. Lack of officers managing state property, lack of coordination internally and externally, training and outreach need to be increased, policy outreach, system improvements and the absence of standard operating procedures (SOP), and if necessary rewards for officers managing assets or state property.